TMIC-14. AUTO-/PARACRINE SIGNALING OF PI3K/AKT/YKL-40 IN MESENCHYMAL GLIOBLASTOMA PROGRESSION. (5th November 2018) - Chen, Apeng; Sharma, Vaibhav; Wang, Qianghu; Agnihotri, Sameer; Kohanbash, Gary; Wang, Y Alan; Pollack, Ian; DePinho, Ronald; Hu, Baoli
Abstract: Glioblastoma multiforme (GBM), the most common and deadliest brain tumor with a median survival of 12–15 months, has been characterized by robust angiogenesis, high invasiveness, and universal recurrence. Genomics and transcriptomics studies defined three GBM subtypes (proneuronal, classical, mesenchymal), which are associated with genomic abnormalities, treatment response, and diversity in tumor microenvironment. However, molecular mechanisms of subtype-specific genotype in contribution to tumor phenotype are less understood. We have previously generated a de novo human GBM model by inactivation of p53 and activation of AKT signaling pathways in human neural stem/progenitor cells (hNSCs). Further characterization of this model indicates that the tumors recapitulate GBM's classical histopathogical features and exhibit a molecular profile resembling the mesenchymal subtype. Comparative transcriptomic analysis revealed that YKL-40/CHI3L1, a secreted glycoprotein, is significantly upregulated during AKT activation induced malignant transformation of hNSCs in vitro and in vivo . Pharmacological inhibition of PI3K/AKT/mTOR signaling pathway results in decreasing YKL-40 mRNA expression and protein secretion level. Mechanistically, motif enrichment analysis and functional validation revealed that YKL-40 is bidirectionally regulated by a gene regulatory network with two transcription factors, BACH2 and CEBPB. Furthermore, YKL-40 significantly activates AKT-S6 and MAPK-ERK kinase signaling pathways, resulting in enhancing tumor cells proliferation, neurosphere and soft-agar colony formation, and tumor progression. In vivo silencing YKL-40 attenuates tumor angiogenesis and prolongs animal survival in the orthotopic xenograft mouse models. Interestingly, knocking down YKL-40 expression decreases microglia/macrophages infiltration in tumor mass. Both in vitro and in vivo validation indicate that PI3K/AKT/YKL-40 mediates tumor-associated microglia/macrophages recruitment and activation during tumor progression. Taken together, these results suggest that auto- and paracrine signaling of PI3K/AKT/YKL-40 affect tumor cells and tumor microenvironment contributing to glioblastoma progression, indicating YKL-40 as a predictive biomarker for evaluation of anti- PI3K/AKT/mTOR therapy, and a potential drug target for the treatment of this devastating disease.